若a0+a1x+a2x^2+a3x^3+a4x^4=(1+2x)4,则a1+a2+a3+a4=?
1个回答
令x=1,
a0+a1x+a2x^2+a3x^3+a4x^4
=a0+a1+a2+a3+a4
=1
相关问题
(1+x)^3=a0+a1x+a2x^2+a3x^3+a4x^4则a1+2a2+3a3+4a4=
若(2x+1)^4=a0x^4+a1x^3+a2x^2+a3x^+a4,则a0-a1+a2-a3+a4的值为?
若a0+a1(2x-1)+a2(2x-1)^2+a3(2x-1)^3+a4(2x-1)^4=x^4,则a2=?
(2012•长沙模拟)若(2-x)4=a0+a1x+a2x2+a3x3+a4x4,则a0-a1+a2-a3+a4=___
若(3x+1)5=a5x5+a4x4+a3x3+a2x2+a1x+a0 则a5-a4+a3-a2+a1-a0和a4+a2
若(2x-1)∧5=a∨5x∧5+a∨4x∧4+a∨3x∧3+a∨2x∧2+a∨1x+a∨0,则a∨2+a∨4=?
若(2x-1)^5=a5x^5+a4x^4+a3x^3+a2x^2+a1x+a0,则a0-a1+a2-a3+a4-a5=
已知(x-1)^4=a4x^4+a3x^3+a2x^2+a1x^1+a0,则a0=_____,a4+a2=______.
若x2+x5=a0+a1(x-1)+a2(x-1)2+a3(x-1)3+a4(x-1)4+a5(x-1)5,则a4=__
1:若(2x^2-3x+1)^3=a0x^6+a1x^5+a2x^4+a3x^3+a4x^2+a5x+a6,则a1+a3